Sexual dysfunction is one of the complications of infertility treatment and is often overlooked in the care of women with infertility - Safarinia, Majid; Mortezai, Zohreh; Alipour, Ahmad (Applied Family Therapy Journal (AFTJ), 2022)
Aim: Sexual dysfunction is one of the complications of infertility treatment and is often overlooked in the care of women with infertility. Therefore, the aim of this study was to determine the effectiveness of self-centered compassion therapy on depression, anxiety and sexual satisfaction in patients. The woman was infertile. Method: This study was a clinical trial study. Fifty-two women with infertility who had sexual dysfunction and referred to the infertility ward of Imam Hossein Hospital in Tehran province from June to September 1400 were selected by purposive sampling. Then they were randomly assigned to the experimental group (under self-centered compassion therapy) (n = 26) and the control group (n = 26). Data collection tools Standard Questionnaire of Sexual Issues (MSQ) Snell and Fisher Walters (1993) were collected in three baseline stages, after intervention and quarterly follow-up. Data analysis was performed using repeated measures multivariate repeated measures analysis of variance. Results: The results showed that in the group under self-centered compassion therapy, the mean score of sexual anxiety and depression as well as sexual satisfaction in the experimental group decreased and increased significantly compared to the control group (P <0.001). Conclusion: The results of this study showed that self-centered compassion therapy can be effective in improving sexual anxiety and depression as well as sexual satisfaction in women with infertility.